BAHASA MELAYU DIALEK SANGGAU - Hardianti, Vivi; Muzammil, Ahmad; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the forms of meaning and noun in the Malay language of Sanggau dialect. The method used is a descriptive method with a qualitative research form. The data of this research is Malay language noun Sanggau dialect used by the people of the City of Sirku. Source of research data in the form of Malay Sanggau dialect spoken by narrative speakers of Sanggau Malay dialect represented by two informants. The techniques used are interview techniques and proficient listening considerations, while the tools used are a list of question, notebooks, and stationery. The results of data analysis of the Malay noun Sanggau dialect, namely, the form of Malay noun Sanggau dialect, there are basic nouns and derived nouns. There are two derivatives, namely affixed nouns and plural nouns. Nouns re-form contained in the Malay language Sanggau dialect that is intact looping, copying sound repetition, and partial looping.Â Keyword: Noun, Malay, my narrative dialect in SanggauÂ